EFEKTIVITAS MEDIA YOUTUBE DALAM MELESTARIKAN PERMAINAN TRADISIONAL DL LSM BENING SAGULING FOUNDATION DI DESA CIHAMPELAS - Tugino, Tugino (IKIP Siliwangi, 2020)
Abstractthis research is based on background. The number of local wisdom that is almost extinct for example traditional games that have a good impact on the growth of children. As we see now, many children do not know the traditional game but know more about online games or what is on each gaget. This study aims to determine the process of managing YouTube's media, in preserving traditional games. The theory used in this study is the concept of PLS, Youtube, traditional games. The researcher formulated three questions related to the title raised, how the responses of the children in LSM Saguling Foundation. yotube media management in LSM saguling foundation In this study researchers used descriptive methods and used a qualitative approach. Data collected through interviews, observation and documentation. As for the population of this study were children who were housed in the clear LSM Saguling Foundation. The results of this study children are less aware of traditional games and LSMplay an active role in preserving traditional games